1997
DOI: 10.1259/bjr.70.830.9135438
|View full text |Cite
|
Sign up to set email alerts
|

Risk of childhood cancer from fetal irradiation.

Abstract: The association between the low dose of ionizing radiation received by the fetus in utero from diagnostic radiography, particularly in the last trimester of pregnancy, and the subsequent risk of cancer in childhood provides direct evidence against the existence of a threshold dose below which no excess risk arises, and has led to changes in medical practice. Initially reported in 1956, a consistent association has been found in many case-control studies in different countries. The excess relative risk obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
299
2
17

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(329 citation statements)
references
References 38 publications
11
299
2
17
Order By: Relevance
“…This unambiguous conclusion is derived from data on Japanese atomic bomb survivors from 1945 who were acutely exposed to up to 4200 mSv 43 and, at a much lower dose level (B10 mSv), from historical data on diagnostic exposure of the fetus from X-ray pelvimetry during pregnancy. 44 Unfortunately, most of these environmental exposures lack a biological rationale or consistent epidemiological evidence. Although there might not be a single or exclusive cause, an abnormal immune response to common infection(s) has emerged as a plausible etiological mechanism for childhood leukemias.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…This unambiguous conclusion is derived from data on Japanese atomic bomb survivors from 1945 who were acutely exposed to up to 4200 mSv 43 and, at a much lower dose level (B10 mSv), from historical data on diagnostic exposure of the fetus from X-ray pelvimetry during pregnancy. 44 Unfortunately, most of these environmental exposures lack a biological rationale or consistent epidemiological evidence. Although there might not be a single or exclusive cause, an abnormal immune response to common infection(s) has emerged as a plausible etiological mechanism for childhood leukemias.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 99%
“…However, epidemiological studies have failed, with one exception, to identify decisively these carcinogens. This exception involves exposure of the unborn child to X-rays in utero, which is associated with a B50% increased risk of childhood leukaemia (Stewart et al, 1956;Stewart and Kneale, 1968;Stewart and Kneale, 1970;Bithell and Stewart, 1975;Doll and Wakeford, 1997;Wakeford and Little, 2003).…”
mentioning
confidence: 99%
“…A follow-up review published in 1987 (12) considered that a causal explanation is supported by evidence indicating an appropriate dose-response relationship, as well as by animal experiments, and concluded that radiation doses on the order of 10 mGy received by the fetus in utero produce a consequent increase in the risk of childhood cancer (12). They reported that the excess absolute risk coefficient is approximately 6% per gray of radiation exposure (12). Historical data from the early days of diagnostic x-ray imaging indicate that malignancies arose from excessive exposure to the x-rays.…”
Section: Radiation Risksmentioning
confidence: 99%